Carbon nanotubes and carbon nanofibers fabricated on tubular porous Al2O3 substrates. (August 2015) - Simon, A.; Seyring, M.; Kämnitz, S.; Richter, H.; Voigt, I.; Rettenmayr, M.; Ritter, U.
Abstract: Carbon nanotubes and carbon nanofibers were grown at different temperatures on porous ceramic Al2 O3 substrates with single channel geometry by means of a chemical vapor deposition technique using methane as carbon source and palladium as catalyst. Time-resolved in-situ Fourier transformed infrared spectroscopy was used for the investigation of methane decomposition for characterizing the catalyst's performance. With increasing synthesis temperature, a structural transition from carbon nanofibers to carbon nanotubes was observed. At a synthesis temperature of 700 °C, solely carbon nanofibers were found, whereas at 800 °C a mixture of two types of bamboo-shaped carbon nanofibers were obtained, suggesting a structural transition. A synthesis temperature to 850 °C results in bamboo-shaped multi-walled carbon nanofibers and multi-walled carbon nanotubes. The carbon products and the observed structural transition were characterized by means of field emission scanning electron microscopy, high-resolution transmission electron microscopy, thermal gravimetric analysis, and Raman spectroscopy.